Mengutip Perjalanan Soenario Sastrowardoyo dalam Menghidupkan Organisasi Kemahasiswaan Islam pada Era 4.0 - Fitri, Diena Fahrani Aisyah; Melinea, Fatihatul Arifiani; Zuhri, Anis Fuadah (Bestari, 2021)
The organization is very necessary in daily activities, especially in the activities of school or university organizations. The organization can not run well if there is no one in the organization that turns it on. As is the case with Soenario Sastriwardoyo, he is a figure who can support his organization with a variety of ideas, one of which is unity. Especially in the 4.0 era where technology has an important role and brings changes to thinking patterns and human activities, especially students. Therefore it is very necessary to study previous history to be able to develop student organizations for the better.